Effect of Endurance Treadmill Training on mIGF-1 Expression and PAX 7 Satellite Cell in Rat Muscle Tissues - Mustofa Mustofa; Karyono Mintaroem; Agustina Endharti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
This study examined the effects of endurance exercise training on muscle Insulin Growth Factor-1 (mIGF-1) and PAX7 transcription factor of satellite cell activation in a tibialis anterior muscle of rat. Rat were subjected to treadmill, divided into three groups, each containing 6 rats. Groups of high, moderate and low doses of exercise received 28, 17 and 12 m/s of treadmill speeds respectively. Treadmill exercise training conducted in 5 days a week within 9 weeks. At the end of 9 weeks of the experiment, rat were sacrificed, tibialis anterior muscle tissues was removed and then subjected to immunohistochemistry examination. There were significant differences in intensity of training in mIGF-1 and PAX7 in muscle tissues (P < 0.05). These results suggested that endurance exercise training which high, moderate and low intensity able to increase mIGF-1 and PAX7 that associates with satellite cell development of muscle tissues.